Integration of Liveworksheets, GeoGebra, and Educaplay in quadratic function learning - Siti Rohani Diniah; Elsa Komala; Sarah Inayah; Folarin Moruf Oluwafemi (Universitas Sarjanawiyata Tamansiswa, 2025)
Learning quadratic functions presents challenges for tenth-grade students, particularly in graph construction and understanding the role of coefficients. This study aims to integrate Liveworksheets, GeoGebra, and Educaplay into quadratic function learning through the development of web-based instructional materials. The study employed the ADDIE development model and involved five subject matter experts, five media experts, and 28 tenth-grade students at SMA Negeri 1 Cibeber during the 2024–2025 academic year. Data were collected using feasibility and effectiveness questionnaires and analyzed descriptively and statistically. The developed materials consist of structured student worksheets incorporating GeoGebra-based interactive activities and Educaplay quizzes. Expert validation results indicate that the materials meet very feasible criteria, while student responses demonstrate very effective criteria. These findings suggest that the integrated web-based materials support students’ conceptual understanding of quadratic functions and promote interactive mathematics learning. In conclusion, the integration of Liveworksheets, GeoGebra, and Educaplay within a unified multimedia system provides an effective and feasible solution to enhance students’ visualization skills, conceptual comprehension, and learning engagement in quadratic function topics. This study contributes theoretically by reinforcing constructivist and technology-integrated learning approaches, methodologically by introducing a three-platform integrated multimedia model within the ADDIE framework, and practically by offering an innovative digital learning alternative aligned with the Merdeka Curriculum and 21st-century mathematics education principles.